FAKTOR YANG MEMPENGARUHI LULUSAN SMA DALAM MEMILIH FAKULTAS EKONOMI PROGRAM STUDI MANAJEMEN UNIVERSITAS BATANGHARI - R. Adisetiawan (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
A quality College is a College that is able to carry its work to improve the quality of, the role and responsibility in education so that the College is not just a container for printing the first undergraduate course, but rather a container to produce scholars who are able to master and apply the discipline. To support the achievement of all of this, the University Batanghari needs to know what factors affect High School graduates in choosing a college. Through this identification, the University can improve all activities and attributes related to the educational process.The results showed that the strategy 4 p's (product, price, place and promotion) that has been established by the University Batanghari overall greatly affect high school students in choosing Course Management Faculty of Economics University Batanghari; While partially a product of factors have the greatest influence in mcmpcngaruhi kcputusan high school students in taking decisions to choose Economics Program study management University Batanghari, therefore University Batanghari should keep trying to improve the quality of education both in teaching systems as well as the quality of the professors who teach, in addition to any educational facilities should continue to be improved such as the addition of economic literature books in the library teaching room facilities, or lab.Keyword: product, price, place and promotion